2021
DOI: 10.2196/27681
|View full text |Cite
|
Sign up to set email alerts
|

Development of a COVID-19 Web Information Transmission Structure Based on a Quadruple Helix Model: Webometric Network Approach Using Bing

Abstract: Background Developing an understanding of the social structure and phenomenon of pandemic information sources worldwide is immensely significant. Objective Based on the quadruple helix model, the aim of this study was to construct and analyze the structure and content of the internet information sources regarding the COVID-19 pandemic, considering time and space. The broader goal was to determine the status and limitations of web information transmissio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Moreover, since the massive shock of the ongoing pandemic has changed the business environment and disrupted the retail industry (22)(23)(24)(25)(26), we argue that it is necessary to consider the role of COVID-19 in our research model. Indeed, literature on changes in consumer behavior is surging (10,11,(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since the massive shock of the ongoing pandemic has changed the business environment and disrupted the retail industry (22)(23)(24)(25)(26), we argue that it is necessary to consider the role of COVID-19 in our research model. Indeed, literature on changes in consumer behavior is surging (10,11,(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the forces of integration and differentiation, it can be expected that the systematicness of the innovative mode of the triple helix model of the university-industry-government relationship will still be in the transitional stage (Leydesdorff, 2012 ), and the quadruple helix (Carayannis & Campbell, 2009 ), quintuple helix (Carayannis & Campbell, 2010 ), and N-tuple helix (Park, 2014 ) appeared successively. For example, Zhu and Park ( 2021 ) used the quadruple helix model to study the network information transmission of COVID-19 and found that multi-helix information sources are insufficient in public health emergencies; especially, educational institutions should be more actively involved in the release of information.…”
Section: Methodsmentioning
confidence: 99%
“…Among scientific inquiries related to our regions of interest, Islam et al [23] assessed agency websites, Facebook, Twitter, and web-based newspapers between December 2019 and April 2020 in 25 languages from 87 countries and found that 82% of the texts included false information. Zhu and Park [24] proposed a quadruple helix model to assess COVID-19-related information circulation. However, these studies omitted several countries in Latin America, the Caribbean, and Africa.…”
Section: Informationscapesmentioning
confidence: 99%